Electrodes, lithium batteries and automobiles
By using a sublayer structure of multi-layer electrode live material in lithium battery electrodes, the hardness gradient of each sublayer is adjusted, and the crack problem caused by uneven force during the rolling process of electrode live material is solved, thereby improving the battery energy density and extending the cycle life.
Patent Information
- Application Number
- JP2024556326
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-03-24
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2043-03-24
AI Technical Summary
When manufacturing lithium batteries, surface cracks in the electrode living material during rolling due to uneven force during the rolling process, affecting the electrode stability and battery performance.
The multi-layer electrode active material sublayer structure is adopted. By adjusting the hardness gradient of each electrode active material sublayer, we ensure that the pressure under each sublayer during the rolling process matches its hardness and avoids cracks.
It effectively improves the particle integrity of the electrode living material and the energy density of the battery, while extending the cycle life of the battery.
Smart Images

Figure 2025510079000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of Chinese Patent Application No. 202210296429.4, entitled "ELECTRODE, LITHIUM BATTERY AND AUTOMOBILE", filed on March 24, 2022. The entire contents of the above application are incorporated herein by reference.
[0002] Field The present disclosure relates to the field of lithium battery technology, and in particular to electrodes, lithium batteries, and automobiles. [Background technology]
[0003] With the development of new energy industry, the market demand for energy density of lithium batteries is increasing. Increasing the compression density of electrodes is one of the important methods to increase the energy density of lithium batteries. However, when the electrode is rolled during the preparation of the electrode, the force of the electrode active material supported on the current collector in the electrode thickness direction becomes uneven, which makes it easy for cracking to occur on the surface layer of the electrode active material particles, affecting the stability of the electrode active material. In addition, the cracked electrode active material consumes more electrolyte, affects the porosity of the electrode, increases the internal resistance of the battery, hinders the battery capacity from being exerted, and may even shorten the battery life. Summary of the Invention [Means for solving the problem]
[0004] A first aspect of the present disclosure provides an electrode. The electrode includes a current collector and an electrode active material layer disposed on at least one side of the current collector. The electrode active material layer includes at least two electrode active material sublayers, the electrode active material sublayers satisfying the following relationship: n×δ i ≦10000, n≧2 and δ i ≦5000, and H i-1 <H i Meet the following.
[0005] n represents the total amount of the electrode active material sublayers, and i is an integer value from 2 to n. i represents the hardness of the i-th electrode active material sublayer, and H1 represents the hardness of the first electrode active material sublayer, both in MPa. The first electrode active material sublayer is in contact with the current collector. δ i represents the absolute value of the hardness difference between the i-th electrode active material sub-layer and the (i-1)th electrode active material sub-layer, and is in MPa.
[0006] Optionally, δ i <=1200.
[0007] Optionally, n, δ i , and the maximum compressed density α of the electrode has the following quantitative relationship: 1.4 g / cm 3 ≦α<1.7g / cm 3 For n ≥ 2 and δ i <= 1000.
[0008] Optionally, n, δ i , and the maximum compressed density α of the electrode has the following quantitative relationship: 2.5 g / cm 3 ≦α<2.75g / cm 3 For n ≥ 2 and δ i <=700.
[0009] Optionally, n, δ i , and the maximum compressed density α of the electrode has the following quantitative relationship: 3.3 g / cm 3 ≦α<3.75g / cm 3 For n ≥ 2 and δ i Meet ≦600.
[0010] Optionally, δ i <= 100.
[0011] Optionally, δ i <=50.
[0012] Optionally, the maximum packed density α of the electrode is 0 g / cm 3 <α<10g / cm 3 Meet the following.
[0013] Optionally, the maximum packed density α of the electrode is 0 g / cm 3 <α<5g / cm 3 Meet the following.
[0014] Optionally, n, δ i , and the maximum compressed density α of the electrode has the following quantitative relationship: 1.3 g / cm 3 ≦α<1.8g / cm 3 , or 2.6 g / cm 3 ≦α<2.8g / cm 3 , or 3.65 g / cm 3 ≦α<5g / cm 3 For n ≥ 10 and δ i Satisfy ≦5.
[0015] Optionally, in an electrode, the absolute value of the hardness difference between any two adjacent electrode active material sublayers is equal.
[0016] Optionally, the electrode is a positive electrode, and the positive electrode is loaded with an active positive electrode material including at least one of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium cobalt oxide, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganese oxygen ternary material, lithium nickel cobalt aluminum oxygen ternary material, and lithium nickel manganese cobalt aluminum oxygen quaternary material.
[0017] Optionally, the electrode is a negative electrode and the negative electrode is loaded with an active negative electrode material comprising at least one of graphite, natural graphite, mesocarbon microbeads, or silicon-carbon anode material.
[0018] Optionally, the electrode is a positive electrode, the positive electrode being loaded with an active positive electrode material, the active positive electrode material comprising a multi-element nickel-containing active material doped with magnesium, the multi-element nickel-containing active material comprising at least one of a lithium nickel cobalt manganese oxygen ternary material, a lithium nickel cobalt aluminum oxygen ternary material, and a lithium nickel manganese cobalt aluminum oxygen quaternary material.
[0019] Optionally, the mass content of elemental magnesium in the magnesium-doped multi-element nickel-containing active material is greater than 0 and less than 4000 ppm.
[0020] Optionally, the lithium nickel cobalt manganese oxygen ternary material has a general structural formula of Li 1+m Ni x Co y Mn 1-x-y O2, where x≧0.33, 0≦y≦0.4, and 0≦m≦0.1.
[0021] Optionally, the general structural formula of the lithium nickel cobalt aluminum oxygen ternary material is Li 1+m Ni x Co y Al 1-x-y O2, where x≧0.33, 0≦y≦0.4, and 0≦m≦0.1.
[0022] Optionally, the general structural formula of the lithium nickel manganese cobalt aluminum oxygen quaternary material is Li 1+m Ni x Co y Mn z Al 1-x-y-z O2, where x≧0.33, 0≦y≦0.4, 0≦z≦0.4, and 0≦m≦0.1.
[0023] Optionally, the value of x is in the range 0.70≦x≦0.98.
[0024] A second aspect of the present disclosure provides a lithium battery comprising an electrode according to the first aspect of the present disclosure.
[0025] A third aspect of the present disclosure provides a vehicle comprising a lithium battery according to the second aspect of the present disclosure. [Brief description of the drawings]
[0026] [Figure 1] FIG. 2 is a schematic diagram of a cross-sectional structure of an electrode according to one embodiment of the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram of a lithium battery according to one embodiment of the present disclosure. [Diagram 3] FIG. 1 is a schematic diagram of a vehicle according to one embodiment of the present disclosure.
[0027] The symbols are as follows: 100-electrode, 10-electrode active material layer, 11-current collector, 101-first electrode active material sublayer, 102-second electrode active material sublayer, 10n-nth electrode active material sublayer, 200-lithium battery, 300-vehicle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The technical solutions of the present disclosure are described in detail below with reference to specific embodiments.
[0029] Generally, the pressed density achievable by each electrode active material is in a certain range. A single electrode active material cannot achieve the maximum pressed density of the electrode while ensuring the particle integrity of the electrode active material. By making an electrode with a hardness gradient, the above-mentioned problem can be effectively solved.
[0030] One embodiment of the present disclosure provides an electrode. The electrode includes a current collector and an electrode active material layer disposed on at least one side of the current collector. The electrode active material layer includes at least two electrode active material sublayers. The electrode active material sublayers satisfy the following relationship: n×δ i ≦10000, n≧2 and δ i ≦5000, and H i-1 <H i (Relationship 1) is satisfied.
[0031] n represents the total amount of the electrode active material sublayers, and i is an integer value from 2 to n. i represents the hardness of the i-th electrode active material sublayer, and H1 represents the hardness of the first electrode active material sublayer, both in MPa. The first electrode active material sublayer is in contact with the current collector. δ i represents the absolute value of the hardness difference between the i-th electrode active material sub-layer and the (i-1)th electrode active material sub-layer, and is in MPa.
[0032] The electrode is provided with a plurality of electrode active material sublayers. The electrode active material sublayer in contact with the current collector is defined as the first electrode active material sublayer. In the thickness direction of the electrode, the sublayers from the current collector side to the surface of the electrode are the second electrode active material sublayer, the third electrode active material sublayer, the fourth electrode active material sublayer, the fifth electrode active material sublayer, ..., the nth electrode active material sublayer, respectively. The hardness of the first electrode active material sublayer to the nth electrode active material sublayer increases gradually (as shown in FIG. 1, the electrode 100 includes a current collector 11 and an electrode active material layer 10 disposed on the current collector 11. The electrode active material layer 10 is formed by a first electrode active material sublayer 101, a second electrode active material sublayer 102, ..., and an nth electrode active material sublayer 10n). By satisfying the absolute value of the hardness difference of the electrode active material sublayers in the relational expression 1, it is possible to ensure that the hardness difference between two adjacent electrode active material sublayers falls within the allowable range. In the process of rolling the electrode, the pressure received by the electrode active material sublayer of the surface layer is the largest. When the pressure is transmitted to the current collector side, the pressure received by the electrode active material sublayer decreases layer by layer. Since the pressure received by each sublayer is consistent with the hardness of the sublayer, the electrode active material in the sublayer is less likely to crack. In this way, the particle integrity of the electrode active material can be ensured while the whole electrode has a high maximum compressed density, thereby improving the energy density of the battery and extending the cycle life of the battery. If the hardness difference of the electrode active material sublayers is too large (does not satisfy the above relational expression 1), the i-th sublayer can withstand a large pressure in the process of rolling the electrode. However, when pressure is applied to the (i-1)th electrode active material sublayer, the pressure received by the (i-1)th electrode active material sublayer is greater than the hardness of the (i-1)th electrode active material sublayer, and as a result, it is impossible to avoid the cracking of the electrode active material in the (i-1)th electrode active material sublayer affecting the performance of the lithium battery.
[0033] In the present disclosure, the electrode active material generally refers to the electrode active material particles, and the cracking of the electrode active material generally refers to the cracking of the electrode active material particles. The hardness of each electrode active material sub-layer can be regarded as the hardness of the electrode active material particles. Specifically, the method for testing the hardness of the electrode active material sub-layer (i.e., the hardness of the electrode active material particles) is as follows.
[0034] (1) Starting from the outermost part of the electrode, the electrode active material particles of each electrode active material sub-layer are individually collected.
[0035] (2) A field emission scanning electron microscope (FESEM) is used to perform a hardness test on a single electrode active material particle. The specific test process involves applying a linearly increasing pressure to a single electrode active material particle using a pointer with a pressure sensor until the electrode active material particle cracks. In this case, the pressure at the tip of the pointer changes suddenly, and an inflection point occurs in the force curve of the electrode active material particle fed back by the pressure sensor. In this case, the pressure on the electrode active material particle is stopped, and the cracking state of the electrode active material particle is observed.
[0036] (3) The pressure value at the inflection point of the force curve is recorded as the cracking pressure of the electrode active material particles. To obtain the hardness value H0 of the electrode active material particles, a calculation is performed according to the following formula: H0 = 2.8P(πr 2 ), where H0 has units of MPa.
[0037] (4) Take at least 500 electrode active material particle samples from each electrode active material sublayer. Test the hardness of each of the at least 500 electrode active material particle samples according to the above steps. Take the arithmetic average of the hardness of the at least 500 electrode active material particles. The arithmetic average is used to refer to the hardness of the corresponding electrode active material sublayer. In particular, when an electrode active material sublayer is a mixture of different electrode active material particles, the hardness of the sublayer is the mass-weighted average hardness value of the electrode active material particles.
[0038] In the present disclosure, δ i represents the absolute value of the hardness difference between the i-th electrode active material sublayer and the (i-1)-th electrode active material sublayer. Specifically, δ2=|H2-H1|, δ3=|H3-H2|, ..., δ n =|H n -H n-1 | and so on. δ i The values of may be the same or different.
[0039] In the present disclosure, each electrode active material sublayer may be formed of a single electrode active material or a mixture of different electrode active materials. The electrode active materials in the electrode active material sublayers may be different or the same. For some specific electrode active materials, the hardness of the electrode active material can be changed by changing the preparation process of the electrode active material or by doping or cladding the electrode active material. Thus, electrodes containing a single type of electrode active material and having a hardness gradient can be prepared.
[0040] In some embodiments of the present disclosure, δ i In some embodiments of the present disclosure, δ i In some embodiments of the present disclosure, δ is ≦100. i ≦50. In this case, the hardness difference between two adjacent electrode active material sub-layers is small, and it is easier to ensure the particle integrity of the electrode active material.
[0041] In some embodiments of the present disclosure, n, δ i , and the maximum compressed density α of the electrode has the following quantitative relationship: 1.4 g / cm 3 ≦α<1.7g / cm 3 For n ≥ 2 and δ i ≦1000;2.5g / cm 3 ≦α<2.75g / cm 3 For n ≥ 2 and δ i ≦700; 3.3g / cm 3 ≦α<3.75g / cm 3 For n ≥ 2 and δ i Meet ≦600.
[0042] In the same case, the greater the total amount n of electrode active material sublayers and / or the smaller the absolute value of the hardness difference between two adjacent layers, the smaller the hardness gradient in the thickness direction of the electrode active material layer. It can be understood that the maximum compressed density α of the electrode is related to the specific type of electrode active material used. When several electrode active materials are selected, the maximum compressed density of the electrode to be fabricated is within the aforementioned specific range (e.g., 1.4 g / cm 3 ≦α<1.7g / cm 3 , or 2.5 g / cm 3 ≦α<2.75g / cm 3 , or 3.3 g / cm 3 ≦α<3.75g / cm 3 ) in n and δ i The values of n and δ i The values of each range (e.g., 1.4 g / cm 3 ≦α<1.7g / cm 3 For n ≥ 2 and δ i ≦1000 and 2.5g / cm 3 ≦α<2.75g / cm 3 For n ≥ 2 and δ i ≦700 and 3.3g / cm 3 ≦α<3.75g / cm 3 For n ≥ 2 and δ i ≦600), which makes the electrode easier to fabricate.
[0043] In this embodiment of the present disclosure, the maximum packed density α of the electrode has a value of 0 g / cm 3 <α<10g / cm 3 In some specific embodiments of the present disclosure, the value of α is 0 g / cm 3 <α<5g / cm 3 Meet the following.
[0044] In some other embodiments of the present disclosure, n, δ, and α have the following quantitative relationship: 3 ≦α<1.8g / cm 3 , or 2.6 g / cm 3 ≦α<2.8g / cm 3 , or 3.65 g / cm3 ≦α<5g / cm 3 For n ≥ 10 and δ i In some other embodiments of the present disclosure, the viscosity is ≦5 g / cm 3 ≦α<10g / cm 3 If n ≧ 15 and δ i ≦2. When n, δ and α satisfy the following quantitative relationship, a high-performance battery can be more easily obtained.
[0045] In some other embodiments of the present disclosure, the absolute value of the hardness difference between any two adjacent electrode active material sublayers in the electrode is equal. Specifically, |H2-H1|=|H3-H2|=...=|H n -H n-1 In this case, the uniformity of the hardness gradient of the electrode can be further improved, and the design of the electrode can be simplified.
[0046] In some embodiments of the present disclosure, the electrode active material includes a positive electrode active material or a negative electrode active material. When the electrode is a positive electrode, the electrode active material can be understood to be a positive electrode active material. When the electrode is a negative electrode, the electrode active material is a negative electrode active material. The positive electrode active material and the negative electrode active material are materials commonly used in the battery field.
[0047] The positive electrode active material includes at least one of, but is not limited to, lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium cobalt oxide, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganese oxygen ternary material, lithium nickel cobalt aluminum oxygen ternary material, lithium nickel manganese cobalt aluminum oxygen quaternary material. The negative electrode active material includes at least one of, but is not limited to, graphite, natural graphite, mesocarbon microbeads, or silicon-carbon anode material. The positive or negative electrode active material may be an undoped or unclad electrode active material, or a doped or clad electrode active material.
[0048] In some embodiments of the present disclosure, the positive electrode active material includes, but is not limited to, a multi-element nickel-containing active material doped with magnesium. The multi-element nickel-containing active material includes, but is not limited to, at least one of a lithium nickel cobalt manganese oxygen ternary material, a lithium nickel cobalt aluminum oxygen ternary material, and a lithium nickel manganese cobalt aluminum oxygen quaternary material. In this disclosure, a multi-element nickel-containing active material refers to a nickel-containing active material that is ternary or higher (generally, ternary or quaternary). NCM stands for lithium nickel cobalt manganese oxygen ternary material. In some embodiments, the general structure of NCM is Li 1+m Ni x Co y Mn 1-x-y O2 (x≧0.33, 0≦y≦0.4, and 0≦m≦0.1). NCA stands for lithium nickel cobalt aluminum oxygen ternary material. In some embodiments, the general structure of NCA is Li 1+m Ni x Co y Al 1-x-y O2 (x≧0.33, 0≦y≦0.4, and 0≦m≦0.1). NCMA stands for lithium nickel manganese cobalt aluminum oxygen quaternary material. In some embodiments, the general structure of NCMA is Li 1+m Ni x Co y Mn z Al 1-x-y-z O2(x≧0.33, 0≦y≦0.4, 0≦z≦0.4, and 0≦m≦0.1).
[0049] In some embodiments of the present disclosure, the value of x ranges from 0.70≦x≦0.98. When the value of x is high, the multi-element nickel-containing material may also be referred to as a "multi-element high-nickel material."
[0050] In some embodiments of the present disclosure, when the electrode active material used is a Mg-doped multi-element nickel-containing active material, the mass content of magnesium element in the magnesium-doped multi-element nickel-containing active material is greater than 0 and less than 4000 ppm.
[0051] Generally, a higher Mg doping amount indicates a higher hardness of the Mg-doped multi-element nickel-containing active material. In the electrode of the present disclosure, the Mg doping amount in the electrode active material sublayers increases continuously from the first electrode active material sublayer to the nth electrode active material sublayer. In this way, the hardness increases sequentially from the first electrode active material sublayer to the nth electrode active material sublayer. Therefore, by simply adjusting the Mg doping amount in the multi-element nickel-containing active material, the hardness of the multi-element nickel-containing active material can be precisely controlled, so that an electrode containing only a single type of active material and having a hardness gradient can be precisely fabricated. Similarly, an electrode containing only a single electrode active material can also be fabricated by doping with other metal elements or in other ways, such as cladding or changing the fabrication process of the electrode active material.
[0052] During the preparation of the electrode, the electrode active material layer may be formed by coating on the surface of the current collector. Coating methods include drip coating, brushing, spraying, dipping, knife coating, and spin coating. The specific coating manner may be determined according to the raw materials of the electrode active material sublayer. The raw materials include the electrode active material, a binder, and an optional conductive agent. The raw materials may be liquid or solid.
[0053] In some embodiments of the present disclosure, the feedstock is a liquid feedstock containing a solvent. The liquid feedstock can be formed on the current collector by drip coating, brushing, spraying, dipping, knife coating, spin coating, etc. In particular, the electrode active material sublayer can be applied layer by layer to the surface of the current collector, and can be applied layer by layer and dried layer by layer to form the electrode active material layer. Alternatively, a multi-layer coating die can be used to apply multiple electrode active material sublayers at once and dried to form the electrode active material layer. In some other embodiments, when the feedstock is a solid feedstock, the solid feedstock can be formed on the current collector by powder spraying, etc. (i.e., the electrode active material layer is made by a dry method).
[0054] Referring to FIG. 2, an embodiment of the present disclosure further provides a lithium battery 200. The lithium battery 200 comprises an electrode 100 according to an embodiment of the present disclosure. In some implementations, the positive electrode of the lithium battery 200 is an electrode 100 according to the present disclosure, and the negative electrode is a conventional pole piece. In some implementations, the negative electrode of the lithium battery 200 is an electrode 100 according to the present disclosure, and the positive electrode is a conventional pole piece. In some implementations, both the positive and negative electrodes in the lithium battery 200 are electrodes 100 according to the present disclosure.
[0055] The battery has excellent energy density and long cycle life.
[0056] 3, an embodiment of the present disclosure further provides an automobile 300. The automobile 300 includes a lithium battery 200 according to an embodiment of the present disclosure. The lithium battery 200 includes an electrode 100 according to an embodiment of the present disclosure. The automobile 300 has a high endurance mileage.
[0057] The examples provided in this disclosure are specifically described below.
[0058] First, a series of ternary nickel-containing materials with different Mg doping amounts (LiNi 0.8 Co 0.1 Mn 0.1Prepare Mg doped NCM811 and measure the hardness of the doped NCM811. When the Mg doping amount is 400 ppm, the hardness of NCM811 is about 100 MPa. When the Mg doping amount is about 700 ppm, the hardness of NCM811 is 125 MPa. When the Mg doping amount is 1000 ppm, the hardness of NCM811 is about 150 MPa. When the Mg doping amount is 1500 ppm, the hardness of NCM811 is about 175 MPa, etc.
[0059] Example 1
[0060] (1) Preparation of the positive electrode: 100 g of NCM811, 1 g of conductive agent Super P, and 0.5 g of binder PVDF5130 are added to N-methylpyrrolidone (NMP) and mixed uniformly to obtain a positive electrode paste. The preset maximum compressed density of the electrode is 3.6 g / cm 3 The positive electrode paste is applied to the surface of the positive electrode current collector-aluminum foil through a three-layer coating die. After drying, rolling, and cutting, a positive electrode with three electrode active material sublayers is obtained. The average particle hardness of the first electrode active material sublayer in the positive electrode is 175 MPa, the average particle hardness of the second electrode active material sublayer is 200 MPa, and the average particle hardness of the third electrode active material sublayer is 225 MPa.
[0061] (2) Preparation of negative electrode: 100g of graphite negative electrode active material, 1g of thickener, and 1g of emulsion are added to water in a specific order and mixed uniformly to obtain a negative electrode active material paste. The negative electrode active material is uniformly applied to the surface of the negative electrode current collector-copper foil. After drying, it is pressed by a roll press machine to obtain a negative electrode. The negative electrode is obtained.
[0062] (3) Battery fabrication: A battery is fabricated by alternately stacking the positive electrodes obtained in step (1), the negative electrodes obtained in step (2), and separators. The positive and negative electrodes are arranged alternately, and adjacent positive and negative electrodes are separated by a separator to obtain a dry battery core. The dry battery core is placed in an aluminum-plastic film exterior body, an electrolyte is injected, and the aluminum-plastic film exterior body is evacuated and sealed, and then left at 60°C for 48 hours. Thereafter, the battery is pressurized at 60°C for secondary packaging, aeration, and liquid separation to obtain a laminated pouch full battery with a capacity of 2.2 Ah. The fabricated battery is designated as S1.
[0063] Example 2
[0064] The difference from Example 1 is that the average particle hardness of the first electrode active material sub-layer in the positive electrode is 175 MPa, the average particle hardness of the second electrode active material sub-layer is 200 MPa, and the average particle hardness of the third electrode active material sub-layer is 250 MPa. The produced battery is designated as S2.
[0065] Example 3
[0066] The difference from Example 1 is that the average particle hardness of the first electrode active material sub-layer in the positive electrode is 175 MPa, the average particle hardness of the second electrode active material sub-layer is 225 MPa, and the average particle hardness of the third electrode active material sub-layer is 250 MPa. The produced battery is designated as S3.
[0067] Example 4
[0068] The difference from Example 1 is that the average particle hardness of the first electrode active material sub-layer in the positive electrode is 100 MPa, and the average particle hardness of the second electrode active material sub-layer is 5100 MPa. The produced battery is designated as S4.
[0069] Example 5
[0070] The difference from Example 1 is that the average particle hardness of the first electrode active material sub-layer in the positive electrode is 175 MPa, the average particle hardness of the second electrode active material sub-layer is 275 MPa, and the average particle hardness of the third electrode active material sub-layer is 375 MPa. The produced battery is designated as S5.
[0071] Example 6
[0072] 100g of NCM811, 1g of conductive agent Super P, and 0.5g of binder PVDF5130 are added to the NMP and mixed uniformly to obtain a positive electrode paste. The preset maximum compressed density of the electrode is 3.6g / cm 3 The positive electrode paste is applied on the surface of the positive electrode current collector-aluminum foil through a single-layer coating die, and then dried and wound for secondary coating until three coating layers are reached. After drying, rolling, and cutting, a positive electrode with three electrode active material sublayers is obtained. The average particle hardness of the first electrode active material sublayer in the positive electrode is 175 MPa, the average particle hardness of the second electrode active material sublayer is 200 MPa, and the average particle hardness of the third electrode active material sublayer is 225 MPa. The fabricated battery is called S6.
[0073] Example 7
[0074] NCM811, conductive agent Super P and binder PVDF5130 are mixed by jet milling, the mixture is heated and electrospun into fibers, and the electrospun material is hot pressed to obtain electrode active material sublayers with different hardness. The mass ratio of NCM811 to Super P to PVDF5130 in the mixture is 100:1:0.5. The maximum preset pressed density of the electrode is 3.6 g / cm 3 The electrode active material sublayers are laminated on the surface of the positive electrode current collector-aluminum foil in order according to hardness, and then hot-pressed, fused, rolled, and cut to obtain a positive electrode including three electrode active material sublayers. The average particle hardness of the first electrode active material sublayer in the positive electrode is 175 MPa, the average particle hardness of the second electrode active material sublayer is 200 MPa, and the average particle hardness of the third electrode active material sublayer is 225 MPa. The battery thus fabricated is designated as S7.
[0075] Example 8
[0076] Add 100g of NCM811, 1g of conductive agent Super P, and 0.5g of binder PVDF5130 to NMP and mix evenly to obtain positive electrode paste. The preset maximum compressed density of the electrode is 3.6g / cm 3 The positive electrode paste is applied on the surface of the aluminum foil through a two-layer coating die. After drying, rolling, and cutting, a positive electrode with two electrode active material sublayers is obtained. The average particle hardness of the first electrode active material sublayer in the positive electrode is 175 MPa, and the average particle hardness of the second electrode active material sublayer is 225 MPa. The fabricated battery is called S8.
[0077] Example 9
[0078] NCM811, conductive agent Super P and binder PVDF5130 are mixed by jet milling, the mixture is heated and electrospun into fibers, and the electrospun material is hot pressed to obtain electrode active material sublayers with different hardness. The mass ratio of NCM811 to Super P to PVDF5130 in the mixture is 100:1:0.5. The maximum preset pressed density of the electrode is 3.65 g / cm 3 The electrode active material sublayers are laminated on the surface of the positive electrode current collector-aluminum foil in order according to hardness, and then hot-pressed, fused, rolled, and cut to obtain a positive electrode including 10 electrode active material sublayers. The average particle hardness of each electrode active material sublayer from the first electrode active material sublayer to the tenth electrode active material sublayer is 175 MPa, 180 MPa, 185 MPa, ..., 220 MPa, in that order. The produced battery is designated as S9.
[0079] Example 10
[0080] NCM811, conductive agent Super P and binder PVDF5130 are mixed by jet milling, the mixture is heated and electrospun into fibers, and the electrospun material is hot pressed to obtain electrode active material sublayers with different hardness. The mass ratio of NCM811 to Super P to PVDF5130 in the mixture is 100:1:0.5. The maximum preset pressed density of the electrode is 3.65 g / cm 3 The electrode active material sublayers are laminated on the surface of the positive electrode current collector-aluminum foil in order according to hardness, and then hot-pressed, fused, rolled, and cut to obtain a positive electrode including 10 electrode active material sublayers. The average particle hardness of each electrode active material sublayer from the first electrode active material sublayer to the tenth electrode active material sublayer is 120 MPa, 140 MPa, 160 MPa, ..., 300 MPa, in that order. The fabricated battery is designated as S10.
[0081] Example 11
[0082] The difference from Example 8 is that the preset maximum compressed density of the electrode is 3.65 g / cm 3 and the number of electrode active material sub-layers in the electrode is 6. The average particle hardnesses of the electrode active material sub-layers from the first electrode active material sub-layer to the sixth electrode active material sub-layer are 175 MPa, 195 MPa, 215 MPa, ..., 275 MPa, in that order. The fabricated battery is designated as S11.
[0083] Example 12
[0084] Lithium iron phosphate (LFP), conductive agent Super P, and binder PVDF5130 are mixed by jet milling, the mixture is heated and electrospun into fibers, and the electrospun material is hot pressed to obtain electrode active material sublayers with different hardness. The mass ratio of LFP to conductive agent to binder is 90:5:5. The maximum preset pressed density of the electrode is 2.65 g / cm. 3The electrode active material sublayers are laminated on the surface of the positive electrode current collector-aluminum foil in order according to hardness, and then hot-pressed, fused, rolled, and cut to obtain a positive electrode including 10 electrode active material sublayers. The average particle hardness of each electrode active material sublayer from the first electrode active material sublayer to the tenth electrode active material sublayer is 175 MPa, 180 MPa, 185 MPa, ..., 220 MPa, in that order. The produced battery is designated as S12.
[0085] Example 13
[0086] The difference from Example 12 is that the preset maximum compressed density of the electrode is 2.5 g / cm 3 The number of electrode active material sublayers of the prepared positive electrode is three. The absolute value δ of the hardness difference between any two adjacent electrode active material sublayers i The pressure in each case was 25 MPa. The battery thus fabricated was designated S13.
[0087] Example 14
[0088] (1) Preparation of negative electrode: 100g of graphite negative electrode active material, 1g of thickener, and 1g of emulsion are added to water in a specific order and mixed uniformly to obtain a negative electrode active material paste. The preset maximum compressed density of the electrode is 1.65g / cm 3 The positive electrode paste is applied to the surface of the negative electrode current collector-aluminum foil through a three-layer coating die. After drying, rolling, and cutting, a negative electrode with 10 layers of electrode active material sublayers is obtained. The average particle hardness of the electrode active material sublayers is 300 MPa, 305 MPa, ..., 345 MPa, respectively.
[0089] (2) Preparation of positive electrode: 100g of NCM811, 1g of conductive agent Super P, and 0.5g of binder PVDF5130 are added to N-methylpyrrolidone (NMP) and mixed uniformly to obtain a positive electrode paste. The positive electrode paste is uniformly applied to the surface of the positive electrode current collector - aluminum foil.
[0090] (3) Battery fabrication: A battery is fabricated by alternately stacking the negative electrodes obtained in step (1), the positive electrodes obtained in step (2), and separators. The positive and negative electrodes are arranged alternately, and adjacent positive and negative electrodes are separated by a separator to obtain a dry battery core. The dry battery core is placed in an aluminum-plastic film exterior body, an electrolyte is injected, and the aluminum-plastic film exterior body is evacuated and sealed, and then left at 60°C for 48 hours. Thereafter, the battery is pressurized at 60°C for secondary packaging, aeration, and liquid separation to obtain a laminated pouch full battery with a capacity of 2.2 Ah. The fabricated battery is designated as S14.
[0091] Example 15
[0092] The difference from Example 14 is that the maximum compressed density of the resulting negative electrode is 1.2 g / cm 3 The number of electrode active material sublayers is three, and the absolute value of the hardness difference between any two adjacent electrode active material sublayers, δ i The pressure in each case was 25 MPa. The battery thus fabricated was named S15.
[0093] Example 16
[0094] The positive electrode prepared in Example 7 and the negative electrode prepared in Example 14 are assembled into a battery S16.
[0095] Example 17
[0096] The difference from Example 15 is that the maximum compressed density of the resulting negative electrode is 1.63 g / cm 3 The number of electrode active material sublayers is two, and the absolute value of the hardness difference between any two adjacent electrode active material sublayers, δ i The obtained battery was named S17.
[0097] To highlight the beneficial effects of the embodiments of the present disclosure, the following comparison is set forth.
[0098] Comparison 1
[0099] NCM811, conductive agent Super P, and binder PVDF5130 are mixed by jet milling, the mixture is heated and electrospun to form fibers, and the electrospun material is hot pressed to obtain an active material layer. The preset maximum compressed density of the electrode is 3.65 g / cm 3 The mass ratio of NCM811 to Super P to PVDF5130 is 100:1:0.5. The active material layer is placed on the positive electrode current collector-aluminum foil and rolled to obtain a positive electrode having one electrode active material sublayer and an average particle hardness of 220 MPa. The battery thus fabricated is called DS1.
[0100] Comparison 2
[0101] NCM811, conductive agent Super P and binder PVDF5130 are mixed by jet milling, the mixture is heated and electrospun into fibers, and the electrospun material is hot pressed to obtain electrode active material sublayers with different hardness. The mass ratio of NCM811 to Super P to PVDF5130 is 100:1:0.5. The preset maximum pressed density of the electrode is 3.65 g / cm. 3 The electrode active material sublayers are laminated on the positive electrode current collector-aluminum foil in order according to hardness, and then hot-pressed, fused, rolled, and cut to obtain a positive electrode including two electrode active material sublayers. The average particle hardness of the first electrode active material sublayer is 10 MPa, and the average particle hardness of the second electrode active material sublayer is 6010 MPa. The battery thus fabricated is designated DS2.
[0102] Comparison 3
[0103] LFP, conductive agent Super P, and binder PVDF5130 are mixed by jet milling. The maximum pre-set pressed density of the electrode is 2.65 g / cm 3 The mixture is heated and electrospun to form fibers, and the electrospun material is hot pressed to obtain pole pieces. A single layer of positive electrode with an average particle hardness of 220 MPa is obtained. The battery thus fabricated is called DS3.
[0104] Comparison 4
[0105] LFP, conductive agent Super P, and binder PVDF5130 are mixed by jet milling, the mixture is heated and electrospun to form fibers, and the electrospun material is hot pressed to obtain pole pieces. The preset maximum compressed density of the electrode is 2.65 g / cm 3 These are laminated in two layers, hot pressed, fused, and rolled to obtain a two-layer positive electrode. The average particle hardness of the first electrode active material sublayer is 10 MPa. The average particle hardness of the second electrode active material sublayer is 6010 MPa. The battery thus fabricated is designated DS4.
[0106] The parameters of the electrodes prepared in the above examples and comparative examples are summarized in Table 1. [Table 1]
[0107] Electrochemical performance testing is performed on the electrodes and batteries fabricated in the above examples and comparisons, including the following test methods.
[0108] (1) The prepared electrode is rolled while gradually increasing the pressure, and the cracking of the electrode active material particles in the electrode is observed and the compressed density of the electrode is measured. When the electrode active material particles crack, the rolling is stopped, and the compressed density measured in the previous experiment is taken as the maximum compressed density α of the electrode. The results are summarized in Table 2.
[0109] (2) Battery cycle performance test: 2.2Ah at 1C, 1) Charge: Charge at 1 / 3C constant current and constant voltage to 4.25V / cell, leave for 30 minutes with cut-off current of 0.05C, (2) Discharge: Discharge at 1 / 3C constant current to 2.5V / cell, leave for 30 minutes, 3) Cycle three times, record the third discharge capacity as the actual capacity C0 of the battery, 4) Charge: Charge at 1C constant current and constant voltage to 4.25V with cut-off current of 0.05C, 5) Leave for 30 minutes, (6) Discharge: Discharge at 1C constant current to 2.5V with actual capacity C0 of the battery, 7) Leave for 30 minutes, 8) Repeat 4) to 7) a total of 500 times. (Note that, since the positive electrode active material used in Examples 12 and 13 and Comparative Examples 3 and 4 was LFP, the upper limit voltage during the test was 3.8 V and the lower limit voltage was 2.0 V.) The measurement results of the capacity retention rate and the direct current resistance under load (DCIR) of the battery after 500 cycles are summarized in Table 3.
[0110] (3) The fully charged batteries S1-S12 and DS1-DS4 are disassembled to obtain the positive electrodes of the batteries S1-S17 and DS1-DS4. A specific amount of electrolyte is added to the positive electrodes. After the electrolyte is completely absorbed, the samples are prepared and subjected to a differential scanning calorimetry (DSC) test. The specific test conditions are as follows: in an air atmosphere, the temperature is increased from room temperature at a rate of 5°C / min, and the thermal decomposition temperature of the electrodes is measured. The results are summarized in Table 4.
[0111] [Table 2]
[0112] [Table 3]
[0113] [Table 4]
[0114] From the data in Tables 2 and 3, it can be seen that the maximum compressed density of the electrode active material in the electrodes provided in Examples 1 to 17 of the present disclosure is close to the preset maximum compressed density while the particle integrity of the electrode active material is maintained. When the materials are the same, the maximum compressed density of the electrodes in the Examples is significantly higher than that in the Comparative Examples. More electrode active material sublayers of the electrodes and smaller hardness difference between adjacent sublayers indicate a larger maximum compressed density of the electrodes (see Examples 9 and 11). When the maximum compressed density of the electrodes is within a suitable range, a larger maximum compressed density indicates a larger energy density of the corresponding battery. However, when the electrode active material of the pole pieces in the batteries is the same, the battery capacity retention rate of the batteries S1 to S17 in the Examples is higher than that in the Comparative Examples, and the DC internal resistance of the batteries in the Examples is relatively small. The thermal decomposition temperature of the positive electrode was measured, and it was found that the thermal decomposition temperature of the positive electrode prepared in the examples was higher than that of the comparative examples when the same electrode active material was used (when the electrode active material is NCM811, see S1 to S11 and S16 in the examples, and DS1 and DS2 in the comparative examples; when the electrode active material is LFP, see S12 and S13 in the examples, and DS3 and DS4 in the comparative examples). It shows that the positive electrode provided in the examples of the present disclosure has better thermal stability and can provide a battery with more stable high-temperature performance and higher safety performance. In particular, although the positive electrodes used in S16 and S7 are the same, there is a difference in thermal decomposition temperature, which is a normal experimental error.
[0115] In conclusion, the electrodes in the embodiments of the present disclosure can be used to provide batteries with high energy density and long cycle life.
[0116] The above description is an exemplary embodiment of the present disclosure. It should be noted that those skilled in the art can make improvements and modifications without departing from the principle of the present disclosure. All such improvements and modifications shall fall within the protection scope of the present disclosure.
Claims
1. An electrode (100) comprising a current collector (11) and an electrode active material layer (10) disposed on at least one side of the current collector (11), the electrode active material layer (10) comprising at least two electrode active material sublayers, the electrode active material sublayers satisfying the following relationship: n×δ i ≦10000, n≧2 and δ i ≦5000, and H i-1 <H i Fulfilling In the formula, n represents the total amount of the electrode active material sublayers, i is an integer value of 2 to n, and H i is the hardness of the i-th electrode active material sublayer, H 1 is the hardness of the first electrode active material sublayer (101), both in MPa, the first electrode active material sublayer (101) being in contact with the current collector (11), δ i is the absolute value of the hardness difference between the i-th electrode active material sub-layer and the (i-1)th electrode active material sub-layer, and is expressed in MPa; electrode (100).
2. δ i 2. The electrode (100) of claim 1, wherein:
3. n, δ i and the maximum compressed density α of the electrode has the following quantitative relationship: 1.4 g / cm 3 ≦α<1.7 g / cm 3 For n ≧ 2 and δ i 2. The electrode (100) of claim 1, wherein:
4. n, δ i and the maximum compressed density α of the electrode has the following quantitative relationship: 2.5 g / cm 3 ≦α<2.75g / cm 3 For n ≧ 2 and δ i 7. The electrode (100) of claim 1, wherein:
5. n, δ i and the maximum compressed density α of the electrode has the following quantitative relationship: 3.3 g / cm 3 ≦α<3.75g / cm 3 For n ≧ 2 and δ i 2. The electrode (100) of claim 1, wherein said electrode (100) satisfies ≦600.
6. δ i 6. The electrode (100) of any one of claims 1 to 5, wherein ≦100.
7. δ i 7. The electrode (100) of any one of claims 1 to 6, wherein the R is ≦50.
8. The maximum compressed density α of the electrode (100) is 0 g / cm 3 <α<10 g / cm 3 The electrode (100) of claim 1 or 2, satisfying
9. The maximum compressed density α of the electrode is 0 g / cm 3 <α<5 g / cm 3 The electrode (100) of claim 7, wherein
10. n, δ i , and α has the following quantitative relationship: 1.3 g / cm 3 ≦α<1.8 g / cm 3 , or 2.6 g / cm 3 ≦α<2.8 g / cm 3 , or 3.65 g / cm 3 ≦α<5 g / cm 3 For n ≧ 10 and δ i The electrode (100) of claim 1, wherein:
11. 11. The electrode (100) of claim 1, wherein the absolute value of the hardness difference between any two adjacent electrode active material sublayers is equal.
12. 12. The electrode (100) of any one of claims 1 to 11, wherein the electrode is a positive electrode and the positive electrode is loaded with an active positive electrode material comprising at least one of lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium cobalt oxide, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganese oxygen ternary material, lithium nickel cobalt aluminum oxygen ternary material, lithium nickel manganese cobalt aluminum oxygen quaternary material.
13. 12. The electrode (100) of any one of claims 1 to 11, wherein the electrode is a negative electrode and the negative electrode is loaded with an active negative electrode material, the active negative electrode material comprising at least one of graphite, natural graphite, mesocarbon microbeads, or silicon-carbon anode material.
14. 12. The electrode (100) of any one of claims 1 to 11, wherein the electrode is a positive electrode, the positive electrode being loaded with an active positive electrode material, the active positive electrode material comprising a multi-element nickel-containing active material doped with magnesium, the multi-element nickel-containing active material comprising at least one of a lithium nickel cobalt manganese oxygen ternary material, a lithium nickel cobalt aluminum oxygen ternary material, or a lithium nickel manganese cobalt aluminum oxygen quaternary material.
15. 15. The electrode (100) of claim 14, wherein the mass fraction of elemental magnesium in the magnesium-doped multi-element nickel-containing active material is greater than 0 and less than 4000 ppm.
16. The general structural formula of the lithium nickel cobalt manganese oxygen ternary material is Li 1+m Ni x Co y Mn 1-x-y O 2 15. The electrode (100) of claim 12 or 14, wherein x≧0.33, 0≦y≦0.4, and 0≦m≦0.
1.
17. The general structural formula of the lithium nickel cobalt aluminum oxygen ternary material is Li 1+m Ni x Co y A 1-x-y O 2 15. The electrode (100) of claim 12 or 14, wherein x≧0.33, 0≦y≦0.4, and 0≦m≦0.
1.
18. The general structural formula of the lithium nickel manganese cobalt aluminum oxygen quaternary material is Li 1+m Ni x Co y Mn z A 1-x-y-z O 2 15. The electrode (100) of claim 12 or 14, wherein x≧0.33, 0≦y≦0.4, 0≦z≦0.4, and 0≦m≦0.
1.
19. 19. The electrode (100) of any one of claims 16 to 18, wherein the value of x is in the range of 0.70≦x≦0.
98.
20. A lithium battery (200) comprising an electrode (100) according to any one of claims 1 to 19.
21. A vehicle (300) comprising the lithium battery (200) of claim 20.
Citation Information
Patent Citations
Electrode plate, electrochemical device and safety coating layer
CN109755670A
Lithium ion battery cathode and lithium ion battery
CN111785921A
Multi-layer negative pole piece and preparation method and application thereof
CN112614969A
High-compaction low-temperature lithium iron phosphate material, lithium battery positive plate and preparation method thereof
CN113086959A
Negative electrode for nonaqueous electrolyte secondary battery
JP2018107060A